Original antigenic sin in dengue - Hoskins effect - Vasantha Kamath; Nisha Davy Olakkengi (Wolters Kluwer Medknow Publications, 2023)
Dengue is a mosquito-borne viral infection found in tropical and subtropical climates worldwide, mostly in urban and semiurban areas. The virus responsible for causing dengue is called dengue virus. There are four dengue virus serotypes, implying that it is possible to be infected four times. While many dengue virus infections produce only mild illness, occasionally, this develops into potentially lethal complications, called severe dengue, dengue hemorrhagic fever, and dengue shock syndrome. Currently, there is no specific treatment for dengue/severe dengue. Due to a rise in mortality rates associated with dengue hemorrhagic fever, severe dengue, and dengue shock syndrome, a better understanding of the reason behind dengue hemorrhagic fever is required. Hence, in this article, we further describe the original antigenic sin in dengue and how the occurrence of Hoskins effect is a major determinant factor for the progression to dengue hemorrhagic fever.